EFFECT OF INFORMATION AND COMMUNICATION TECHNOLOGY ON THE ATTAINMENT OF MILLENNIUM DEVELOPMENT GOALS (MDGS) IN NIGERIA, (A CASE STUDY OF PAMPAIDA MILLENNIUM VILLAGE, KADUNA STATE, NIGERIA. (FUDMA JOURNAL OF SCIENCES, 2021)
The study examines the effects of information and communication technology (ICT) on the attainment of the Millennium Development Goals (MDGs) in Nigeria from 2006 to 20015 with specific focus on effects of mobile phone, Internet, Computer and Radio on MDGs. Four research questions and four hypotheses were tested at 5% level of significance. The design for this study was a survey design while the population was made up of Five Thousand Six Hundred and Sixty-Six (5,666) people living in Pampaida Millennium Village. The sample size was Three Hundred and Seventy-Four (374). The sampling technique used is convenient sampling. The method of data collection used was questionnaire for primary data. Method of data analysis were percentages, linear regression and analysis of variance. The data analysis revealed that the ICT factors that have meaningful impact on MDGs were Mobile phones, Internet and Radio. Mobile phones were the widely use ICTs within the study area followed by Radio and Internet respectively. Computer usage within the village was quite low; this calls for integration of computer education in adult and non-formal system of education, which is the major source of education within the community
Keywords: effects, information and communication, Millennium Development Goals